O contexto social da avaliação de desempenho: um levantamento em uma instituição bancária - Dickel, Giovani Andre (2017)
This research studied the influence of the social context, (measured through the constructs quality of the relation and participation); of the concepts (rating) in the evaluation, with the reaction of those evaluated in the process of evaluation of performance appraisal to which the employees were submitted in a Brazilian banking institution. The general objective was to verify if the aspects related to the social context had a greater impact on the reaction of the evaluated ones than the rating received in the evaluation. This is a quantitative survey carried out with 4,374 bank branches, out of a total of 5,428 branches owned by that institution. The analysis was carried out from a cross section, with data related to the evaluative process of the first semester of 2016. The results pointed to the existence of significance of the variables in the relations of the presented model. Overall, the linear regression test showed that the independent variables present in the model explained 31.73% of the variability of the construct Reaction to Evaluation, with the explanatory power of the variables related to the constructs Participation (26.68%) and Relationship Quality (25,92%), higher values than those obtained by the variables included in the Concepts in the Evaluation (13.40%) construct. The results validate empirically the theoretical model that reports the importance of the social context for the performance appraisal, and serve as a subsidy for the development of performance appraisal systems in organizations.